Unipolar injection currents in Bi₄Ge₃O₁₂ crystals - Bochkova, T.M.; Plyaka, S.N.; Sokolyanskii, G.Ch. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
Current-voltage characteristics of bismuth orthogermanate (Bi₄Ge₃O₁₂) single crystals have been measured at different temperatures under conditions of unipolar injection of charge carriers. It has been found that conduction is characterized by the existence of two channels of the percolation. The temperature dependencies of the conductivity, mobility and concentration of the electrons and holes are considered. The obtained results are discussed in terms of hopping transport model of charge carriers in doped heavily compensated semiconductors.